2021
DOI: 10.3389/fcvm.2021.688522
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Soluble ST2 Are Associated With Plaque Vulnerability in Patients With Non-ST-Elevation Acute Coronary Syndrome

Abstract: Background: Recent studies have suggested that soluble suppression of tumorigenicity-2 (sST2), an inflammation-related protein receptor, is associated with atherosclerotic diseases. This study aimed to investigate the potential predictive value of sST2 on plaque vulnerability by assessing whether elevated serum levels of sST2 are associated with vulnerable plaque features in patients with non-ST-elevation acute coronary syndrome (ACS).Methods: A total of 120 patients with non-ST-elevation ACS (167 lesions) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
3
6
0
1
Order By: Relevance
“…In the face of this evolution, one should expect that patients on maintenance HD present a longer period of a pro-atherosclerotic calcification status; thus, they most likely would present the final stage of atherosclerotic plaque evolution, plaque macrocalcification. Considering that mitral valve calcification mechanisms are similar to the ones from large plaque calcifications, our results seem natural and confirm the previous published data, as elevated sST2 levels seem to be correlated with spotty calcifications and not with large ones [ 47 ]. These results require further confirmation in prospective studies with larger number of patients in order to reduce bias and/or positive results due to chance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the face of this evolution, one should expect that patients on maintenance HD present a longer period of a pro-atherosclerotic calcification status; thus, they most likely would present the final stage of atherosclerotic plaque evolution, plaque macrocalcification. Considering that mitral valve calcification mechanisms are similar to the ones from large plaque calcifications, our results seem natural and confirm the previous published data, as elevated sST2 levels seem to be correlated with spotty calcifications and not with large ones [ 47 ]. These results require further confirmation in prospective studies with larger number of patients in order to reduce bias and/or positive results due to chance.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies evaluated the imbrication of sST2 and atherosclerotic plaque calcifications. For instance, Luo showed that in patients with non-ST-elevated acute coronary syndrome, higher levels of sST2 were associated with spotty atherosclerotic calcifications, and those with lower levels exhibited large plaque calcifications [ 47 ]. In our study, there is a negative connection between sST2 levels and mitral valve calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above studies, Luo et al prospectively enrolled 120 patients to assess plaque vulnerability by coronary computed tomography angiography (CCTA) ( 26 ). Their study showed that higher serum sST2 levels were associated with higher plaque vulnerability.…”
Section: Association With Coronary Atherosclerotic Burdenmentioning
confidence: 99%
“…Correlation analysis revealed significant positive associations between sST2 and CACS for both CACS groups (Pearson r=0.288, p=0.036 for CACS=0; Pearson r=0.237, p=0.039 for CACS>0). Luo et al reported similar results in patients with non-ST-elevation acute coronary syndrome [36]. They found higher serum sST2 levels among patients with spotty plaque calcification, than those with large calcification.…”
Section: Discussionmentioning
confidence: 68%